2011
DOI: 10.1007/s11524-011-9572-7
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Testing of a New Socioeconomic Status Measure Based on Housing Data

Abstract: Socioeconomic status (SES) has been associated with many health outcomes. Commonly used datasets such as medical records often lack data on SES but do include address information. The authors sought to determine whether an SES measure derived from housing characteristics is associated with other SES measures and outcomes known to be associated with SES. The data come from a telephone survey of parents/ guardians of children aged 1-17 years who resided in Olmsted County, Minnesota, and Jackson County, Missouri.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(161 citation statements)
references
References 25 publications
4
156
0
1
Order By: Relevance
“…More than 75% of the adult respondents were women, and 89% of the subjects were white (median age, 41 years). The sociodemographic characteristics of the study subjects’ children were previously reported 29. Overall, except for gender, the sociodemographic characteristics of the study subjects were similar to Olmsted County population as a whole.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…More than 75% of the adult respondents were women, and 89% of the subjects were white (median age, 41 years). The sociodemographic characteristics of the study subjects’ children were previously reported 29. Overall, except for gender, the sociodemographic characteristics of the study subjects were similar to Olmsted County population as a whole.…”
Section: Resultssupporting
confidence: 54%
“…Details have been described previously 29. Olmsted County is located 90 miles southeast of Minneapolis.…”
Section: Methodsmentioning
confidence: 99%
“…Some research has been conducted in the Olmsted County population to develop new surrogate mea-sures of socioeconomic status to be used for stratification or for adjustment in statistical analyses. 55,56 CONCLUSION Extrapolations and generalizations from studies in any single selected population must be judged on a study-by-study basis and should consider specific demographic or socioeconomic variables relevant to the study question. We provide an example of analyses and comparisons that may guide the generalization of epidemiological findings from a single population to other populations or to the entire United States.…”
Section: Generalizations From Olmsted County Epidemiological Studiesmentioning
confidence: 99%
“…For women who were residents of Olmsted County, MN, the team calculated the HOUsing-based SES measures index (HOUSES), a validated socioeconomic measure. HOUSES is a composite index that is derived from individual housing features (housing value, square footage, and the number of bedrooms and bathrooms) by linking address information of patients to enumerated real property data that are available from the Assessor's Office of local government; higher values represent better socioeconomic status (18). Information regarding personal history of thyroid disease (not on thyroid hormone therapy), diabetes mellitus, hypertension, pregnancy loss, and preterm delivery was also collected.…”
Section: Study Measures/assessmentsmentioning
confidence: 99%